Analisis Penerapan Standar Akutansi Keuangan Program Pensiun Manfaat Pasti Dalam Kaitannya Dengan Kewajaran Laporan Keuangan Pada Yayasan Dana Pensiun Karyawan Krakatau Steel - Fadillah, Adil (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
Yayasan Dana Pensiun Karyawan Krakatau Steel (YDPK-KS) is a foundation founded by PT. Krakatau steel to run the pension program for all of its employers. The recording and reporting of the pension fund activities are stated in statement of standard of financial accounting number 18. in carrying out its accounting activities, YDPK-KS refers to the statement mentioned above so that the financial report made by YDPK-KS may be stated by the public accounting